Perancangan Sistem Informasi Posyandu Ibu Dan Anak Berbasis Web - Barany Fachri; Hendry Hendry; Muhammad Zen (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
Tomuan Holbung Village is a village in North Sumatra. As a village, there is still information that has not been accessed by many other people through public communication, namely the internet. Where there is a Posyandu currently has a meaningful role to support public health services. The role of the Posyandu is accompanied by the increasingly visible role of the community after the emergence of the Posyandu as a form of community-based health effort. Apart from that, Posyandu activities have been running smoothly so far because of the Posyandu Information System (SIP) book as an implementation guide. Technology contributes to structuring management systems and work processes in government and private agencies. One of the applications of Information Technology in village life is the use of a web-based Mother and Child Posyandu Information System. In this design, the web-based Posyandu information system is analysis, design, coding and testing as well as entity relationship diagrams in designing the database. The Posyandu information system is equipped with a web-based display so that users can adjust the contents in the system as a means of information in designing a web-based Mother and Child Posyandu Information System in Tomuan Holbung Village.